Effects of Spray Drying, Freeze Drying and Gamma Irradiation on the Antioxidant Activities of Camel and Cow Milk Fractions - Harizi N. (2023)
This work aimed to establish an integrated approach to investigate the total phenolic content and antioxidant activities of dried skim camel and cow milk and their fractions. The milk fractions were obtained by acid or enzymatic coagulation followed by spray drying (inlet temperature/outlet temperature: 125 ± 2 °C/90 ± 2 °C) or freeze drying (−50 °C, 0.05 mbar) coupled or not to gamma irradiation (at 5, 11, 22 kGy). The results showed that the total phenolic content (measured in gallic acid equivalent, GAE) varied depending on the drying technique. The freeze-drying process corresponded to the highest values of total phenolic compounds, with 247.23 ± 2.08 mg GAE/100 g powder for the β-casein fraction of camel milk (βC CaM) and 621.13 ± 4.16 mg GAE/100 g powder for the β-casein fraction of cow milk (βC CoM). Compared to spray-dried fractions, freeze-dried fractions showed generally higher ferric reducing antioxidant power for both camel milk and cow milk. The highest values of free radical scavenging activity were seen in the spray-dried β-casein fractions of camel milk (βC CaM) and cow milk (βC CoM) and in the freeze-dried acid whey of cow and camel milk (AW CaM and AW CaM). Freeze-dried acid whey (AW CaM and AW CoM) appeared to be less sensitive to gamma irradiation at 5 and 11 kGy.